Empowering women through political participation: an examination of indian rural women’s perceptions - Rezaul Karim, Mohammad; Sultana, Nazma; Awal , Abdul (Interacción y Perspectiva, 2024)
The purpose of this study was to investigate how rural women in Dinhata Subdivision perceived women’s empowerment through political engagement. The research was carried out in the Indian district of Coochbehar’s Dinhata Sub-Division. It is a quantitative and qualitative research. Purposive sampling was used, and semi-structured interviews with rural women in the study region were used to gather qualitative data. Data were analyzed quantitatively after deductive coding according to quantitative themes. According to the report, there are divergent opinions among rural women on how political engagement may empower women. While the majority of rural women (47%) believe that women should actively participate in politics to empower themselves, 29% see this negatively and 24% have no notion how women might empower themselves through politics. Nonetheless, 67% of women in rural areas are eager to get involved in politics. They also opine that male members of the family will have no objection if they participate in politics actively. Additionally, they see certain obstacles if they become actively involved in politics, such as taking care of the family and doing housework, which are traditionally and culturally reserved for women in rural India.